Living to Save Taxes - Marcus Eliason; Henry Ohlsson (Uppsala University, Department of Economics, 2007)
Does taxation affect the timing of death? This is important as an example of how behavior might be affected by economic incentives. We study how three changes in Swedish inheritance taxation 2004-2005 have affected daily all-cause mortality. Our first main result is that mortality decreased by 16 percent the day before the beginning of expected tax reductions. Second, there was no corresponding effect before an unexpected tax reduction.
urn:nbn:se:uu:diva-25382
Keywords: D64; H24; I19; 330; Behavioral responses to taxation; estate tax; inheritance tax; tax avoidance; timing of death; Steuerreform; Erbschaftsteuer; Steuersenkung; Sterblichkeit; Schweden